Self-assembled microsphere molecular sieve with hierarchical pore structure and preparation method of self-assembled microsphere molecular sieve

By preparing self-assembled microsphere molecular sieves with a microporous-mesoporous-macroporous structure, the problems of low catalytic activity and difficult separation of MFI molecular sieves have been solved, realizing easy separation and high mass transfer and diffusion capabilities of large-sized molecular sieves, which are suitable for chemical and functional materials fields.

CN119591123APending Publication Date: 2025-03-11ORDOS LABORATORY +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411646712.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing MFI molecular sieves have low catalytic activity and are prone to carbon deposition and deactivation. Furthermore, small-sized molecular sieves are difficult to separate, have cumbersome operation, and generally have poor mass transfer capabilities.

Method used

A self-assembled microsphere molecular sieve with a microporous-mesoporous-macroporous structure was prepared by hydrolyzing a mixture of organic template agent, aluminum source and silicon source to form nanosheet stacked microspheres. The template agent was removed by calcination, which simplified the process.

Benefits of technology

It achieves easy separation and excellent mass transfer and diffusion capabilities for large-size molecular sieves, simplifies the production process, and is suitable for chemical and functional materials fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005139866340000161
    Figure BDA0005139866340000161
  • Figure BDA0005139866340000171
    Figure BDA0005139866340000171
  • Figure BDA0005139866340000172
    Figure BDA0005139866340000172
Patent Text Reader

Abstract

The invention belongs to the technical field of molecular sieve research, and particularly discloses a self-assembled microsphere molecular sieve with a hierarchical pore structure and a preparation method thereof, the molecular sieve comprises at least one microsphere, each microsphere comprises a plurality of mutually stacked primary particles, the primary particles are composed of mutually crossed and stacked nano sheet layers, and the nano sheet layers are stacked in a staggered manner. The microspheres have a porous structure, and the porous structure comprises micropores, mesopores and macropores; the pore diameter of the micropores is 0.5 nm to 2 nm, the pore diameter of the mesopores is 2 nm to 30 nm, and the pore diameter of the macropores is 50 nm to 300 nm; the average particle size of the molecular sieve is 5-20 [mu] m. Therefore, the molecular sieve is simple in synthesis process, products are easy to collect, ultra-high-speed centrifugal separation is not needed, process conditions are greatly simplified, industrial large-scale production is facilitated, and the molecular sieve has good catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of molecular sieve research, and specifically relates to a self-assembled microsphere molecular sieve with a multi-level pore structure and a preparation method thereof. Background Art

[0002] MFI molecular sieve is one of the most important molecular sieve catalytic materials at present due to its unique pore structure, good thermal stability, suitable adjustable acid center density and excellent shape-selective catalysis, and its typical representative is ZSM-5 molecular sieve. However, due to the low catalytic activity of MFI molecular sieve and the easy deactivation of catalyst due to carbon deposition, the application of this material in catalytic reactions is limited. Although many small-sized nanosheet molecular sieves with strong mass transfer capacity have been prepared in the related technology, there are still some problems, such as difficult separation, cumbersome operation, and general mass transfer capacity. Therefore, the preparation method of molecular sieve microspheres with developed multi-level pore structure needs further study. Summary of the invention

[0003] This application is based on the inventor's discovery and understanding of the following facts and problems:

[0004] In view of the above problems, the inventors have found that the average particle size of the MFI molecular sieve in the related art is generally 100nm to 2μm. If the average particle size of the molecular sieve is too small, it is not easy to separate in the actual application process. Therefore, if you want to make a large-sized molecular sieve, you need to add an adhesive to make micron-sized spherical particles, which is a cumbersome operation. Therefore, the inventors envisioned the preparation of a large-sized MFI molecular sieve, which should have a microporous-mesoporous-macroporous pore structure and a nanosheet structure, so that it is easy to separate and has excellent mass transfer and diffusion capabilities.

[0005] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes a self-assembled microsphere molecular sieve with a multi-level pore structure and a preparation method thereof, which has a simple synthesis process, is easy to collect products or has good catalytic performance.

[0006] In the first aspect of the present application, a molecular sieve is proposed, comprising at least one microsphere, each of which comprises a plurality of mutually stacked primary particles, wherein the primary particles are composed of mutually cross-stacked nanosheet layers, and the microsphere has a porous structure, wherein the porous structure comprises micropores, mesopores and macropores; the micropore diameter is 0.5nm to 2nm, the mesopore diameter is 2nm to 30nm, and the macropore diameter is 50nm to 300nm; the average particle size of the molecular sieve is 5μm to 20μm.

[0007] Therefore, the molecular sieve has both micropore-mesopore-macroporous structure and nanosheet structure, and has the advantages of adjustable pore size and structure, making it easy to separate while also having excellent mass transfer and diffusion capabilities, thus having important application prospects in the fields of chemical industry and functional materials.

[0008] In some embodiments, the average particle size of the primary particles is 100 nm to 700 nm; in other embodiments, the average particle size of the primary particles is 100 nm to 400 nm, thereby further improving the mass transfer capacity of the molecular sieve.

[0009] In some embodiments, the thickness of the nanosheet layer is 2 nm to 40 nm, thereby improving the mass transfer capacity of the molecular sieve nanosheet layer.

[0010] In some embodiments, the BET specific surface area of ​​the molecular sieve is 550 m 2 ·g -1 ~750m 2 ·g -1 , the total pore volume is 0.40cm 3 ·g -1 ~0.60cm 3 ·g -1 The micropore volume is 0.10cm 3 ·g -1 ~0.20cm 3 ·g -1 . This can further improve the mass transfer diffusion capacity and catalytic performance of the molecular sieve.

[0011] In some embodiments, the composition of the molecular sieve includes SiO2 and Al2O3.

[0012] The second aspect of the present application provides a method for preparing a molecular sieve, comprising:

[0013] Mixing an organic template, an aluminum source, a silicon source and deionized water to obtain a first mixed solution;

[0014] The aluminum source and the silicon source in the first mixed solution are fully hydrolyzed, and then the generated alcohol is removed, and deionized water is added to the obtained alcohol removal product to obtain a second mixed solution containing a molecular sieve precursor;

[0015] Crystallizing the molecular sieve precursor to obtain molecular sieve raw powder;

[0016] The organic template agent in the molecular sieve raw powder is removed to obtain the molecular sieve.

[0017] The above-mentioned preparation method of the present application has a simple synthesis process, and the product is easy to collect, and does not require ultra-high-speed centrifugation separation, which greatly simplifies the process conditions and is conducive to large-scale industrial production. The prepared molecular sieve has the advantages of adjustable pore size and structure and good catalytic performance, and has important application prospects in the fields of chemical industry and functional materials.

[0018] In some embodiments, after obtaining the first mixed solution, the first mixed solution may be mixed with a self-assembly regulator.

[0019] In some embodiments, the self-assembly regulator includes at least one of an organic amine or a surfactant, the organic amine includes at least one of ethylenediamine, n-butylamine, and hexadecyltrimethylammonium bromide; the surfactant includes at least one of sodium dodecyl sulfate, polyvinyl alcohol, Tween-20, and Tween-80. Thus, the source of the material is wide, and the self-assembly state of the primary particles can be adjusted to form microspheres of different sizes or densities.

[0020] In some embodiments, the molar ratio of the self-assembly regulator to the silicon source is 0.03 to 0.8: 1. This can further regulate the structure of the molecular sieve microspheres.

[0021] In some embodiments, the organic template comprises a tetrabutylphosphine hydroxide aqueous solution with a mass concentration of 30% to 50%. This can guide the MFI type molecular sieve to have a lamellar structure.

[0022] In some embodiments, the aluminum source includes at least one of aluminum isopropoxide, aluminum hydroxide, aluminum sulfate, sodium metaaluminate, and aluminum sulfate 18hydrate. Thus, the material source is wide and the cost is low.

[0023] In some embodiments, the silicon source includes at least one of tetraethyl orthosilicate, silica sol, white carbon black, and silicic acid. Thus, the material source is wide and the cost is low.

[0024] In some embodiments, the molar ratio of the silicon source, the organic template, the deionized water and the aluminum source is 1: 0.03-0.4: 7-80: 0.001-0.1, thereby making the reaction more complete and improving the reaction efficiency.

[0025] In some embodiments, the alcohol removal comprises stirring at 50° C. to 120° C. for 5 to 24 hours, thereby completely removing the ethanol, which is beneficial for the self-assembly of the nanosheets to form molecular sieve microspheres.

[0026] In some embodiments, the crystallization temperature is 120° C. to 170° C., and the crystallization time is 12 hours to 168 hours, thereby facilitating the improvement of the crystallization rate.

[0027] In some embodiments, the organic template agent is removed by calcination, the calcination temperature is 500° C. to 600° C., and the calcination time is 5 h to 9 h, thereby removing the organic template agent and improving the purity of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the X-ray diffraction pattern of the molecular sieve microspheres prepared in Example 1 of the present application.

[0029] Figure 2 These are N2 physical adsorption-desorption curves of the molecular sieve microspheres prepared in Example 1 of the present application, (a) N2 desorption isotherm, (b) N2 adsorption isotherm.

[0030] Figure 3 This is a scanning electron microscope image of the molecular sieve microspheres prepared in Examples 1 and 2 of the present application.

[0031] Figure 4 The scanning electron microscope image (a) and the transmission electron microscope image (b) of the nanosheet molecular sieve prepared as a comparative example of the present application. DETAILED DESCRIPTION

[0032] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.

[0033] In the first aspect of the present application, a molecular sieve is proposed, comprising at least one microsphere, each of which comprises a plurality of mutually stacked primary particles, wherein the primary particles are composed of mutually cross-stacked nanosheet layers, and the microsphere has a porous structure, wherein the porous structure comprises micropores, mesopores and macropores; the micropore diameter is 0.5nm to 2nm, the mesopore diameter is 2nm to 30nm, and the macropore diameter is 50nm to 300nm; the average particle size of the molecular sieve is 5μm to 20μm.

[0034] It can be understood that the molecular sieve microspheres are self-assembled by stacking molecular sieve nanosheets with controllable thickness and density. They have a micropore-mesopore-macroporous structure, which can show faster reaction rates in macromolecular reactions. At the same time, they have a larger size, making them easy to separate in separation and analysis applications. They have important application prospects in the fields of chemical industry, functional materials, etc.

[0035] Among them, pore size refers to the shape and size of the pores in porous solids. In fact, the pores are very irregular, and they are usually regarded as circles and their radius is used to represent the size of the pores. The pore size test method is: in a liquid nitrogen environment, by injecting and pumping gas into the sample tube, the desorption amount and adsorption-desorption isotherm of each partial pressure point are measured, and then the pore size is calculated using BJH and other theoretical calculations. Generally speaking, the desorption isotherm is closer to the thermodynamically stable state, so the desorption isotherm is often used to calculate the pore size distribution; the average particle size refers to the average particle size calculated by converting the projection area of ​​500 random particles tested by scanning electron microscopy into a standard circle of equal area.

[0036] In some embodiments, the average particle size of the molecular sieve is 5 μm to 20 μm. For example, the average particle size of the molecular sieve can be 5 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or 20 μm, etc. Among them, the average particle size of the molecular sieve can be regulated by adjusting the content of the organic amine or surfactant. If the average particle size of the molecular sieve is too large, the reaction rate will be reduced; if the average particle size is too small, it will be difficult to separate during practical application. Within the above average particle size range, the molecular sieve has a relatively large size, is easy to separate in separation and analysis applications, and has good catalytic performance.

[0037] In some embodiments, the average particle size of the primary particles is 100 nm to 700 nm; in other embodiments, the average particle size of the nanosheet layer is 100 nm to 400 nm. For example, the average particle size of the nanosheet layer can be 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm or 700 nm, etc. This can further improve the mass transfer capacity of the molecular sieve.

[0038] In some embodiments, the thickness of the nanosheet layer is 2nm to 40nm, for example, 2nm, 5nm, 8nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm or 40nm. If the nanosheet layer is too thick, the mass transfer capacity is poor; if the nanosheet layer is too thin, the mechanical strength and stability of the molecular sieve are low. The thickness of the nanosheet layer can be adjusted by adjusting the ratio of the silicon source and the aluminum source, thereby improving the mass transfer capacity of the molecular sieve nanosheet layer.

[0039] The average particle size of primary particles refers to the average particle size calculated by converting the projected area of ​​500 random primary particles constituting microspheres into a standard circle of equal area tested by scanning electron microscopy. The thickness of the nanosheet layer refers to the thickness of the nanosheet layer constituting the primary particles along the b-axis direction, and the thickness of the nanosheet layer of 500 random primary particles along the b-axis direction is tested by transmission electron microscopy.

[0040] In some embodiments, the BET specific surface area of ​​the molecular sieve is 550 m 2 ·g -1 ~750m 2 ·g -1 (e.g. 550m 2 ·g -1 、600m 2 ·g -1 、650m 2 ·g -1 、700m 2 ·g -1 or 750m 2 ·g -1 etc.), with a total pore volume of 0.40 cm 3 ·g -1 ~0.60cm 3 ·g -1 (such as 0.40cm 3 ·g -1 、0.45cm 3 ·g -1 、0.50cm 3 ·g -1 、0.55cm 3 ·g -1 or 0.60cm 3 ·g -1 The micropore volume is 0.10cm 3 ·g -1 ~0.20cm 3 ·g -1 (such as 0.10cm 3 ·g -1 、0.12cm 3 ·g -1 、0.14cm 3 ·g -1 、0.16cm 3 ·g -1 、0.18cm 3 ·g -1 or 0.20cm 3 ·g -1 This can further improve the mass transfer and diffusion capacity and catalytic performance of the molecular sieve.

[0041] It should be noted that the specific surface area refers to the total area per unit mass of the material. The test method for the specific surface area is as follows: in a liquid nitrogen environment, by injecting and pumping gas into the sample tube, the nitrogen isothermal adsorption-desorption curve is measured, and the data in the range of P / P0=0.05-0.35 in the nitrogen isothermal adsorption-desorption curve is taken, and the single-layer adsorption data V is obtained after processing using the BET formula. m, and then calculate the specific surface area based on this.

[0042] In some embodiments, the components of the molecular sieve include SiO2 and Al2O3, which are in a composite state in the molecular sieve framework after synthesis.

[0043] The second aspect of the present application provides a method for preparing a molecular sieve, comprising:

[0044] S1: Mixing an organic template, an aluminum source, a silicon source and deionized water to obtain a first mixed solution.

[0045] Specifically, the organic template can be diluted with deionized water and stirred at room temperature for 0.1 to 0.5 hours to obtain a uniform mixed solution; then the aluminum source and the silicon source are slowly added to the uniform mixed solution and stirred at room temperature for 0.5 to 1 hour to obtain a first mixed solution.

[0046] In some embodiments, the organic template comprises a tetrabutylphosphine hydroxide aqueous solution with a mass concentration of 30% to 50%. For example, the mass concentration of the tetrabutylphosphine hydroxide aqueous solution can be 30%, 35%, 40%, 45% or 50%, etc. Wherein, the tetrabutylphosphine hydroxide can inhibit the growth in the b-axis direction while guiding the molecular sieve framework structure, so that it forms a nanosheet layered structure.

[0047] In some embodiments, the aluminum source includes at least one of aluminum isopropoxide, aluminum hydroxide, aluminum sulfate, sodium aluminate, and aluminum sulfate 18hydrate; and the silicon source includes at least one of tetraethyl orthosilicate, silica sol, white carbon black, and silicic acid. Thus, the material sources are wide and the cost is low.

[0048] In some embodiments, the silicon source is calculated by the amount of SiO2, and the aluminum source is calculated by the amount of Al2O3. The molar ratio of the silicon source, the organic template, the deionized water and the aluminum source is 1:0.03-0.4:7-80:0.001-0.1, for example, it can be 1:0.03:22:0.04, 1:0.03:22:0.08, 1:0.09:22:0.04, 1:0.4:80:0.1 or 1:0.4:7:0.001, etc. Within the above ratio range, the reaction can be made more sufficient, the reaction efficiency can be improved, and the structure of the molecular sieve can be adjusted by adjusting the ratio. Among them, too little organic template will affect the crystallinity, and too much organic template will further reduce the size of the primary particles; too little water content will affect the polymerization between the primary particles of the molecular sieve, and too much water content will cause the thickness of the nanosheet layer to increase.

[0049] S2: fully hydrolyzing the aluminum source and the silicon source in the first mixed solution, then removing the generated alcohol, and adding deionized water to the obtained alcohol removal product to obtain a second mixed solution containing a molecular sieve precursor.

[0050] It is understandable that during the synthesis process, the hydrolysis of tetraethyl orthosilicate will produce ethanol. If the ethanol is not completely removed, it will affect the polymerization between the primary particles and ultimately affect the assembly of the molecular sieve nanosheet primary particles into microspheres.

[0051] In some embodiments, the alcohol removal step includes stirring at 50°C to 120°C (such as 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, etc.) for 5 hours to 24 hours (such as 5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours or 24 hours, etc.). During the stirring process, all ethanol and a small amount of water will be evaporated and removed, and deionized water needs to be added to the liquid level before alcohol removal after the stirring is completed. The alcohol removal step is extremely important in the entire synthesis process, because ethanol will induce secondary nucleation and produce new primary crystal structures during the crystal synthesis process, thereby inhibiting the aggregation between particles, so it is necessary to completely remove ethanol.

[0052] In some embodiments, after obtaining the first mixed solution, the first mixed solution may be mixed with a self-assembly regulator.

[0053] In some embodiments, the self-assembly regulator includes an organic amine or a surfactant. The organic amine includes at least one of ethylenediamine, n-butylamine, and hexadecyltrimethylammonium bromide; the surfactant includes at least one of sodium dodecyl sulfate, polyvinyl alcohol, Tween-20, and Tween-80. Thus, the source of the material is wide, and the self-assembly state of the primary particles can be adjusted to form microspheres of different sizes or densities.

[0054] In some embodiments, the molar ratio of the organic amine or the surfactant to the silicon source is 0.03 to 0.8:1, for example, 0.03:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1 or 0.8:1, etc. This can further regulate the structure of the molecular sieve microspheres. As the amount of organic amine or surfactant added increases, the gap between the primary particles of the self-assembled microspheres becomes smaller, and the density of the microspheres becomes denser.

[0055] S3: crystallizing the molecular sieve precursor to obtain molecular sieve raw powder.

[0056] Specifically, the crystallization comprises: transferring the second mixed liquid to a stainless steel reactor with a polytetrafluoroethylene lining, placing it in an oven for constant temperature crystallization, and after the crystallization is completed, filtering, washing and drying the obtained product for multiple times to obtain the molecular sieve raw powder.

[0057] In some embodiments, the crystallization temperature is 120° C. to 170° C. (e.g., 120° C., 130° C., 140° C., 150° C., 160° C., or 170° C.), and the crystallization time is 12 h to 168 h (e.g., 12 h, 24 h, 36 h, 48 h, 60 h, 72 h, 84 h, 96 h, 120 h, 140 h, or 168 h). The above temperature and time are conducive to improving the crystallization rate.

[0058] S4: removing the organic template agent from the molecular sieve raw powder to obtain the molecular sieve.

[0059] In some embodiments, the organic template is removed by calcination, the calcination temperature is 500°C to 600°C (such as 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C or 600°C, etc.), the calcination time is 5h to 9h (such as 5h, 6h, 7h, 8h or 9h, etc.), and the heating rate is 1 to 5°C / minute. In this way, the organic template can be removed and the purity of the product can be improved.

[0060] The above-mentioned preparation method of the present application has a simple synthesis process, the product is easy to collect, and the prepared molecular sieve has the advantages of adjustable pore size and structure, and has important application prospects in the fields of chemical industry, functional materials, etc.

[0061] The embodiments of the present application are described in detail below.

[0062] Example 1

[0063] (1) diluting the organic template agent tetrabutylphosphine hydroxide (TBPOH) with deionized water, stirring at room temperature for 0.5 hours to obtain a uniform mixed solution;

[0064] (2) slowly adding sodium aluminate and tetraethyl orthosilicate to the above uniform mixed solution, stirring at room temperature for 1 hour, the silicon source is calculated by SiO2 amount, the aluminum source is calculated by Al2O3 amount, the molar ratio of silicon source, organic template, deionized water and aluminum source is 1:0.03:22:0.04, stirring at room temperature for 2 hours to obtain a uniform mixed solution;

[0065] (3) adding ethylenediamine (EDA) to the mixed solution obtained in step (2), wherein the molar ratio of ethylenediamine to silicon source is n(EDA):n(SiO2)=0.1:1;

[0066] (4) stirring the mixed solution obtained in step (3) at 80° C. for 12 hours to evaporate and completely remove the alcohol, and after the stirring is completed, adding deionized water to the liquid level before the alcohol removal;

[0067] (5) transferring the mixed solution after the alcohol removal in step (4) to a stainless steel reactor lined with polytetrafluoroethylene, and placing it in a 150° C. oven for constant temperature crystallization for 72 hours. After the crystallization is completed, the obtained product is filtered, washed, and dried multiple times to obtain the self-assembled nanosheet MFI molecular sieve microsphere raw powder;

[0068] (6) The original powder of the self-assembled nanosheet MFI molecular sieve microspheres was dried and calcined at 550°C for 6 hours at a heating rate of 2°C / min to remove the organic template to obtain self-assembled nanosheet MFI molecular sieve microspheres with micropores, mesopores and macropores.

[0069] Example 2

[0070] (1) diluting the organic template agent tetrabutylphosphine hydroxide (TBPOH) with deionized water, stirring at room temperature for 0.5 hours to obtain a uniform mixed solution;

[0071] (2) slowly adding sodium aluminate and tetraethyl orthosilicate to the above uniform mixed solution, stirring at room temperature for 1 hour, the silicon source is calculated by SiO2 amount, the aluminum source is calculated by Al2O3 amount, the molar ratio of silicon source, organic template, deionized water and aluminum source is 1:0.03:22:0.04, stirring at room temperature for 2 hours to obtain a uniform mixed solution;

[0072] (3) adding ethylenediamine (EDA) to the mixed solution obtained in step (2), wherein the molar ratio of ethylenediamine to silicon source is n(EDA):n(SiO2)=0.25:1;

[0073] (4) stirring the mixed solution obtained in step (3) at 80° C. for 12 hours to evaporate and completely remove the alcohol, and after the stirring is completed, adding deionized water to the liquid level before the alcohol removal;

[0074] (5) transferring the mixed solution after the alcohol removal in step (4) to a stainless steel reactor lined with polytetrafluoroethylene, and placing it in a 150° C. oven for constant temperature crystallization for 72 hours. After the crystallization is completed, the obtained product is filtered, washed, and dried multiple times to obtain the self-assembled nanosheet MFI molecular sieve microsphere raw powder;

[0075] (6) The original powder of the self-assembled nanosheet MFI molecular sieve microspheres was dried and calcined at 550°C for 6 hours at a heating rate of 2°C / min to remove the organic template to obtain self-assembled nanosheet MFI molecular sieve microspheres with micropores, mesopores and macropores.

[0076] Example 3

[0077] (1) diluting the organic template agent tetrabutylphosphine hydroxide (TBPOH) with deionized water, stirring at room temperature for 0.5 hours to obtain a uniform mixed solution;

[0078] (2) slowly adding sodium aluminate and tetraethyl orthosilicate to the above uniform mixed solution, stirring at room temperature for 1 hour, the silicon source is calculated by SiO2 amount, the aluminum source is calculated by Al2O3 amount, the molar ratio of silicon source, organic template, deionized water and aluminum source is 1:0.03:22:0.04, stirring at room temperature for 2 hours to obtain a uniform mixed solution;

[0079] (3) stirring the mixed solution obtained in step (2) at 80° C. for 12 hours to evaporate and completely remove the alcohol, and after the stirring is completed, adding deionized water to the liquid level before the alcohol removal;

[0080] (4) transferring the mixed solution after the alcohol removal in step (3) to a stainless steel reactor lined with polytetrafluoroethylene, and placing it in a 150° C. oven for constant temperature crystallization for 72 hours. After the crystallization is completed, the obtained product is filtered, washed, and dried multiple times to obtain the original powder of self-assembled nanosheet MFI molecular sieve microspheres;

[0081] (5) The original powder of the self-assembled nanosheet MFI molecular sieve microspheres was dried and calcined at 550°C for 6 hours at a heating rate of 2°C / min to remove the organic template to obtain self-assembled nanosheet MFI molecular sieve microspheres with micropores, mesopores and macropores.

[0082] Example 4

[0083] (1) diluting the organic template agent tetrabutylphosphine hydroxide (TBPOH) with deionized water, stirring at room temperature for 0.5 hours to obtain a uniform mixed solution;

[0084] (2) slowly adding aluminum sulfate 18hydrate and tetraethyl orthosilicate into the above uniform mixed solution, stirring at room temperature for 1 hour, the silicon source is calculated by SiO2 amount, the aluminum source is calculated by Al2O3 amount, the molar ratio of silicon source, organic template, deionized water and aluminum source is 1:0.03:22:0.08, stirring at room temperature for 2 hours to obtain a uniform mixed solution;

[0085] (3) adding ethylenediamine (EDA) to the mixed solution obtained in step (2), wherein the molar ratio of ethylenediamine to silicon source is n(EDA):n(SiO2)=0.5:1;

[0086] (4) stirring the mixed solution obtained in step (3) at 80° C. for 12 hours to evaporate and completely remove the alcohol, and after the stirring is completed, adding deionized water to the liquid level before the alcohol removal;

[0087] (5) transferring the mixed solution after the alcohol removal in step (4) to a stainless steel reactor lined with polytetrafluoroethylene, and placing it in a 150° C. oven for constant temperature crystallization for 72 hours. After the crystallization is completed, the obtained product is filtered, washed, and dried multiple times to obtain the self-assembled nanosheet MFI molecular sieve microsphere raw powder;

[0088] (6) The original powder of the self-assembled nanosheet MFI molecular sieve microspheres was dried and calcined at 550°C for 6 hours at a heating rate of 2°C / min to remove the organic template to obtain self-assembled nanosheet MFI molecular sieve microspheres with micropores, mesopores and macropores.

[0089] Example 5

[0090] (1) diluting the organic template agent tetrabutylphosphine hydroxide (TBPOH) with deionized water, stirring at room temperature for 0.5 hours to obtain a uniform mixed solution;

[0091] (2) slowly adding sodium aluminate and tetraethyl orthosilicate to the above uniform mixed solution, stirring at room temperature for 1 hour, the silicon source is calculated by SiO2 amount, the aluminum source is calculated by Al2O3 amount, the molar ratio of silicon source, organic template, deionized water and aluminum source is 1:0.09:22:0.04, stirring at room temperature for 2 hours to obtain a uniform mixed solution;

[0092] (3) adding ethylenediamine (EDA) to the mixed solution obtained in step (2), wherein the molar ratio of ethylenediamine to silicon source is n(EDA):n(SiO2)=0.1:1;

[0093] (4) stirring the mixed solution obtained in step (3) at 80° C. for 12 hours to evaporate and completely remove the alcohol, and after the stirring is completed, adding deionized water to the liquid level before the alcohol removal;

[0094] (5) transferring the mixed solution after the alcohol removal in step (4) to a stainless steel reactor lined with polytetrafluoroethylene, and placing it in a 150° C. oven for constant temperature crystallization for 72 hours. After the crystallization is completed, the obtained product is filtered, washed, and dried multiple times to obtain the self-assembled nanosheet MFI molecular sieve microsphere raw powder;

[0095] (6) The original powder of the self-assembled nanosheet MFI molecular sieve microspheres was dried and calcined at 550°C for 6 hours at a heating rate of 2°C / min to remove the organic template to obtain self-assembled nanosheet MFI molecular sieve microspheres with micropores, mesopores and macropores.

[0096] Example 6

[0097] (1) diluting the organic template agent tetrabutylphosphine hydroxide (TBPOH) with deionized water, stirring at room temperature for 0.5 hours to obtain a uniform mixed solution;

[0098] (2) slowly adding sodium aluminate and tetraethyl orthosilicate to the above uniform mixed solution, stirring at room temperature for 1 hour, the silicon source is calculated by SiO2 amount, the aluminum source is calculated by Al2O3 amount, the molar ratio of silicon source, organic template, deionized water and aluminum source is 1:0.03:22:0.04, stirring at room temperature for 2 hours to obtain a uniform mixed solution;

[0099] (3) adding cetyltrimethylammonium bromide (CTAB) to the mixed solution obtained in step (2), wherein the molar ratio of cetyltrimethylammonium bromide to silicon source is n(CTAB):n(SiO2)=0.15:1;

[0100] (4) stirring the mixed solution obtained in step (3) at 80° C. for 12 hours to evaporate and completely remove the alcohol, and after the stirring is completed, adding deionized water to the liquid level before the alcohol removal;

[0101] (5) transferring the mixed solution after the alcohol removal in step (4) to a stainless steel reactor lined with polytetrafluoroethylene, and placing it in a 150° C. oven for constant temperature crystallization for 72 hours. After the crystallization is completed, the obtained product is filtered, washed, and dried multiple times to obtain the self-assembled nanosheet MFI molecular sieve microsphere raw powder;

[0102] (6) The original powder of the self-assembled nanosheet MFI molecular sieve microspheres was dried and calcined at 550°C for 6 hours at a heating rate of 2°C / min to remove the organic template to obtain self-assembled nanosheet MFI molecular sieve microspheres with micropores, mesopores and macropores.

[0103] Example 7

[0104] (1) diluting the organic template agent tetrabutylphosphine hydroxide (TBPOH) with deionized water, stirring at room temperature for 0.5 hours to obtain a uniform mixed solution;

[0105] (2) slowly adding sodium aluminate and tetraethyl orthosilicate to the above uniform mixed solution, stirring at room temperature for 1 hour, the silicon source is calculated by SiO2 amount, the aluminum source is calculated by Al2O3 amount, the molar ratio of silicon source, organic template, deionized water and aluminum source is 1:0.03:22:0.04, stirring at room temperature for 2 hours to obtain a uniform mixed solution;

[0106] (3) adding sodium dodecyl sulfate (SDS) to the mixed solution obtained in step (2), wherein the molar ratio of sodium dodecyl sulfate to silicon source is n(SDS):n(SiO2)=0.15:1;

[0107] (4) stirring the mixed solution obtained in step (3) at 80° C. for 12 hours to evaporate and completely remove the alcohol, and after the stirring is completed, adding deionized water to the liquid level before the alcohol removal;

[0108] (5) transferring the mixed solution after the alcohol removal in step (4) to a stainless steel reactor lined with polytetrafluoroethylene, and placing it in a 150° C. oven for constant temperature crystallization for 72 hours. After the crystallization is completed, the obtained product is filtered, washed, and dried multiple times to obtain the self-assembled nanosheet MFI molecular sieve microsphere raw powder;

[0109] (6) The original powder of the self-assembled nanosheet MFI molecular sieve microspheres was dried and calcined at 550°C for 6 hours at a heating rate of 2°C / min to remove the organic template to obtain self-assembled nanosheet MFI molecular sieve microspheres with micropores, mesopores and macropores.

[0110] Example 8

[0111] (1) diluting the organic template agent tetrabutylphosphine hydroxide (TBPOH) with deionized water, stirring at room temperature for 0.5 hours to obtain a uniform mixed solution;

[0112] (2) slowly adding sodium aluminate and tetraethyl orthosilicate to the above uniform mixed solution, stirring at room temperature for 1 hour, the silicon source is calculated by SiO2 amount, the aluminum source is calculated by Al2O3 amount, the molar ratio of silicon source, organic template, deionized water and aluminum source is 1:0.03:22:0.04, stirring at room temperature for 2 hours to obtain a uniform mixed solution;

[0113] (3) Add ethylenediamine (EDA) to the mixed solution obtained in step (2), wherein the molar ratio of ethylenediamine to silicon source is n(EDA):n(SiO2)=0.1:1.

[0114] (4) stirring the mixed solution obtained in step (3) at 80° C. for 12 hours to evaporate and completely remove the alcohol, and after the stirring is completed, adding deionized water to the liquid level before the alcohol removal;

[0115] (5) transferring the mixed solution after the alcohol removal in step (4) to a stainless steel reactor with a polytetrafluoroethylene liner, placing it in a 120° C. oven for constant temperature crystallization for 168 hours, and after the crystallization is completed, filtering, washing, and drying the obtained product multiple times to obtain the self-assembled nanosheet MFI type molecular sieve microsphere raw powder;

[0116] (6) The original powder of the self-assembled nanosheet MFI molecular sieve microspheres was dried and calcined at 550°C for 6 hours at a heating rate of 2°C / min to remove the organic template to obtain self-assembled nanosheet MFI molecular sieve microspheres with micropores, mesopores and macropores.

[0117] Comparative Example

[0118] (1) diluting the organic template agent tetrabutylphosphine hydroxide (TBPOH) with deionized water, stirring at room temperature for 0.5 hours to obtain a uniform mixed solution;

[0119] (2) slowly adding sodium aluminate and tetraethyl orthosilicate to the above uniform mixed solution, stirring at room temperature for 1 hour, the silicon source is calculated by SiO2 amount, the aluminum source is calculated by Al2O3 amount, the molar ratio of silicon source, organic template, deionized water and aluminum source is 1:0.03:22:0.04, stirring at room temperature for 2 hours to obtain a uniform mixed solution;

[0120] (3) transferring the mixed solution obtained in step (2) to a stainless steel reactor lined with polytetrafluoroethylene, placing it in a 150° C. oven for constant temperature crystallization for 72 hours, and after the crystallization is completed, filtering, washing, and drying the obtained product multiple times to obtain the self-assembled nanosheet MFI molecular sieve microsphere raw powder;

[0121] (4) The self-assembled nanosheet MFI molecular sieve microsphere raw powder was dried and calcined at 550° C. for 6 hours at a heating rate of 2° C. / min to remove the organic template to obtain the MFI nanosheet molecular sieve.

[0122] The experimental conditions of the embodiments and comparative examples are shown in Table 1, and the test results are shown in Table 2:

[0123] Table 1 Experimental conditions

[0124]

[0125]

[0126] Table 2 Test results

[0127]

[0128] 1) Take the MFI molecular sieve microspheres obtained in Example 1 as test samples, and characterize their crystal structure by X-ray diffraction characterization. The results are as follows Figure 1 As shown, the sample exhibits the characteristic diffraction peaks of typical MFI molecular sieves.

[0129] 2) The MFI molecular sieve microspheres obtained in Example 1 were taken as test samples, and the pore structure was characterized by N2 physical adsorption and desorption method. The results are as follows: Figure 2 shown.

[0130] 3) The MFI molecular sieve microspheres obtained in Examples 1 and 2 were taken as test samples, and their crystal morphology was characterized using a scanning electron microscope. Figure 3As shown, both samples showed a microsphere morphology formed by self-assembly of nanosheet MFI molecular sieves, and due to the increase in the amount of ethylenediamine added, the packing density of the self-assembled crystal small particles on the surface of the microspheres of Example 2 was smaller.

[0131] 4) The nanosheet MFI molecular sieve obtained in the comparative example was taken as a test sample, and its crystal morphology was characterized by scanning electron microscopy and transmission electron microscopy. Figure 4 As shown, the sample has a nanosheet structure, but the small crystal particles do not self-assemble to form microspheres.

[0132] In the description of the present application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0133] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0134] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A molecular sieve, characterized in that: The invention comprises at least one microsphere, each of which comprises a plurality of mutually stacked primary particles, wherein the primary particles are composed of mutually cross-stacked nanosheet layers, and the microsphere has a porous structure, wherein the porous structure comprises micropores, mesopores and macropores; The micropore diameter is 0.5nm to 2nm, the mesopore diameter is 2nm to 30nm, and the macropore diameter is 50nm to 300nm; The average particle size of the molecular sieve is 5 μm to 20 μm.

2. The molecular sieve according to claim 1, characterized in that The average particle size of the primary particles is 100 nm to 700 nm, preferably 100 nm to 400 nm.

3. The molecular sieve according to claim 1, characterized in that The thickness of the nanosheet layer is 2nm-40nm.

4. The molecular sieve according to claim 1, characterized in that Satisfy at least one of the following conditions: The BET specific surface area of ​​the molecular sieve is 550 m 2 ·g -1 ~750m 2 ·g -1 ; The total pore volume is 0.40 cm 3 ·g -1 ~0.60cm 3 ·g -1 ; The micropore volume is 0.10 cm 3 ·g -1 ~0.20cm 3 ·g -1 .

5. The molecular sieve according to claim 1, characterized in that The components of the molecular sieve include SiO2 and Al2O3.

6. A method for preparing the molecular sieve according to any one of claims 1 to 5, characterized in that: include: Mixing an organic template, an aluminum source, a silicon source and deionized water to obtain a first mixed solution; The aluminum source and the silicon source in the first mixed solution are fully hydrolyzed, and then the generated alcohol is removed, and deionized water is added to the obtained alcohol removal product to obtain a second mixed solution containing a molecular sieve precursor; Crystallizing the molecular sieve precursor to obtain molecular sieve raw powder; The organic template agent in the molecular sieve raw powder is removed to obtain the molecular sieve.

7. The method according to claim 6, characterized in that After obtaining the first mixed solution, the first mixed solution may be mixed with a self-assembly regulator.

8. The method according to claim 7, characterized in that The self-assembly regulator includes at least one of an organic amine or a surfactant.

9. The method according to claim 8, characterized in that The organic amine includes at least one of ethylenediamine, n-butylamine and hexadecyltrimethylammonium bromide; and / or The surfactant includes at least one of sodium lauryl sulfate, polyvinyl alcohol, Tween-20 and Tween-80.

10. The method according to claim 7, characterized in that The molar ratio of the self-assembly regulator to the silicon source is 0.03-0.8:

1.

11. The method according to claim 6, characterized in that Satisfy at least one of the following conditions: The organic template comprises a tetrabutylphosphine hydroxide aqueous solution with a mass concentration of 30% to 50%; The aluminum source includes at least one of aluminum isopropoxide, aluminum hydroxide, aluminum sulfate, sodium metaaluminate, and aluminum sulfate 18hydrate; The silicon source includes at least one of tetraethyl orthosilicate, silica sol, white carbon black and silicic acid.

12. The method according to claim 6, characterized in that The molar ratio of the silicon source, the organic template, the deionized water and the aluminum source is 1: 0.03-0.4: 7-80: 0.001-0.

1.

13. The method according to claim 6, characterized in that The alcohol removal includes stirring at 50° C. to 120° C. for 5 to 24 hours.

14. The method according to claim 6, characterized in that The crystallization temperature is 120° C. to 170° C., and the crystallization time is 12 h to 168 h.

15. The method according to claim 6, characterized in that The organic template agent is removed by calcination, the calcination temperature is 500° C. to 600° C., and the calcination time is 5 hours to 9 hours.

Citation Information

Cited By

  • Method for synthesizing microspherical boron-containing mercerizing molecular sieve

    CN120288798A